2009
DOI: 10.1016/j.humimm.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Lack of significant de novo HLA allosensitization in ventricular assist device recipients transfused with leukoreduced, ABO identical blood products

Abstract: Ventricular assist devices provide support for a failing heart and often serve as a bridge to transplantation. The use of these devices has also been associated with allosensitization to HLA antigens because of transfusion of blood products. Our program established a protocol mandating the use of leukoreduced, irradiated and ABO identical products, including platelets, in patients receiving initial implantations of VAD as a bridge to transplantation. Recipients were tested for anti-HLA antibodies before VAD im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…During the work-up phase, patients receive multiple transfusions that increase the risk of antibody development and can affect the ability of the patient to receive a future heart transplant. 16 Most importantly, despite recent improvements in technology, the traditional algorithms we use to treat GIB were primarily designed for the general population and are not specific for VAD patients. Technology has seen many improvements during the last decade, especially when examining the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…During the work-up phase, patients receive multiple transfusions that increase the risk of antibody development and can affect the ability of the patient to receive a future heart transplant. 16 Most importantly, despite recent improvements in technology, the traditional algorithms we use to treat GIB were primarily designed for the general population and are not specific for VAD patients. Technology has seen many improvements during the last decade, especially when examining the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…The positive reactions converted to negative when sera were pre-incubated with albumin-coated beads. Similarly, serum from VAD patients tested in our laboratory [12] exhibited reactivity in ELISA assays, but reactivity occurs even in wells that do not contain HLA antigen, indicating false positive reactions.…”
Section: Evolution Of Antibody Testing Systemsmentioning
confidence: 77%
“…The same group [11] later presented a larger cohort of HeartMate recipient (n=71) analyzing the effect of leuko-reduced blood products, but found no significant effect. Our laboratory [12] reported a series of 55 VAD recipients, most of whom had received a pulsatile device. Our center only uses leuko-reduced, irradiated, and ABO matched blood products and we observed minimal allosensitization.…”
Section: Volume Displacement Pumpsmentioning
confidence: 99%
“…This low incidence of refractoriness is likely due to our protocol that from 1990 onward mandated transfusion of only leukoreduced, ABO identical platelets for all patients at high risk of platelet transfusion refractoriness. 4,79 …”
Section: Methodsmentioning
confidence: 99%
“…7,8 Cardiac surgery patients with a ventricular assist device receiving only leukoreduced, ABO identical transfusions have a reduced risk of HLA-A,B allosensitization in one observational study. 9 A retrospective, observational cohort study of cardiac surgical patients demonstrated that patients receiving only ABO identical platelets had fewer red cell and platelet transfusions, a shorter length of hospital stay, fewer days of postoperative fever, fewer days on antibiotics, fewer hours in the ICU, one third the in-hospital mortality, and lower hospital costs and charges when compared to patients receiving ABO non-identical platelets. 10 Transfusion of ABO non-identical components, in preliminary reports, has been associated with an increase in red cell transfusions in blunt trauma patients 11 and in surgical patients overall.…”
Section: Introductionmentioning
confidence: 99%